Planning by design (PxD) based systematic methodologies - Butuner, Hakan; Taylor and Francis (Boca Raton, FL : Auerbach Publications, an imprint of Taylor and Francis, 2017)
The book shows how to use Planning by Design (PxD) for developing working models to any type of subject area. Section 1 describes the nature of planning in general, the formula of planning, the features that make it systematic, the essence of PxD, and developing and using the working model. Section 2 demonstrates personal application of creative planning to real life cases and practical working models on different subject areas. The book provides a general planning master guide that shows how to develop a working model of any definable subject matter. This objective will be accomplished by introducing the concepts, the process, and the methodology of PxD.
Cover -- Half Title -- Title Page -- Copyright Page -- Dedication -- Contents -- Preface -- Author -- I: Planning by Design (PxD) -- 1: Nature of Planning -- 2: Formula for Planning -- 3: Systematic Planning -- 4: Essence of Planning by Design -- II: Sample Systematic Methodologies -- 5: Systematic Marketing Innovation Planning (SMIP) -- 6: Systematic Competency-Based Training Needs Analysis (SCTNA) -- 7: Systematic Wide Area Network Planning? (SWANP) -- 8: skyscraPer terrorist attack resPonse Planning (starP) -- 9: Systematic Planning of Globalizing Local Firms (SPG) -- References -- Index.
Keywords: Business planning; Planning; COMPUTERS / Information Technology; TECHNOLOGY & ENGINEERING / Industrial Engineering